2021
DOI: 10.1089/tmr.2021.0028
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Telehealth Physical Therapy Among Patients with Chronic Low Back Pain

Abstract: Background: Coronavirus disease 2019 prompted the rapid adoption of telehealth to provide physical therapy. Patients' perceptions about telehealth physical therapy are mostly unknown. This study describes perceptions of telehealth physical therapy among patients with chronic low back pain (LBP). Methods: This study surveyed participants in an ongoing multisite clinical trial of nonpharmacological LBP treatments. Participants were asked about their willingness to use telehealt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…This study corroborates that regular exercise in a home-based program significantly reduces pain, with further reductions observed when face-to-face supervision sessions are added. These findings align with the existing literature [ 39 , 40 , 41 ]. However, it is noteworthy that some studies reported less pronounced improvements [ 40 , 41 ], possibly due to participants starting with lower pain levels [ 39 , 41 , 42 ] or the postintervention follow-up duration being shorter [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study corroborates that regular exercise in a home-based program significantly reduces pain, with further reductions observed when face-to-face supervision sessions are added. These findings align with the existing literature [ 39 , 40 , 41 ]. However, it is noteworthy that some studies reported less pronounced improvements [ 40 , 41 ], possibly due to participants starting with lower pain levels [ 39 , 41 , 42 ] or the postintervention follow-up duration being shorter [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…These findings align with the existing literature [ 39 , 40 , 41 ]. However, it is noteworthy that some studies reported less pronounced improvements [ 40 , 41 ], possibly due to participants starting with lower pain levels [ 39 , 41 , 42 ] or the postintervention follow-up duration being shorter [ 39 ]. Albadalejo et al [ 43 ] reached similar conclusions, noting that incorporating health education classes altered subjective pain perception.…”
Section: Discussionsupporting
confidence: 92%
“…The survey was conducted in September to October of 2020. Among survey respondents, 9% indicated that access to technology would have been a barrier to telehealth participation, while 43% indicated they would be unwilling to participate in PT delivered via telehealth, compared to 24% indicating unwillingness to participate in telehealth behavioral health sessions [ 31 ]. These findings lessened concerns about technology access but supported the concern that shifting to telehealth delivery would differently impact the OPTIMIZE interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Implementation of this device for home use outside of clinical settings does not preclude adequate supervision, which is needed to monitor safety, encourage proper movement, and improve adherence. Recent research suggested that education is needed to enhance acceptance of telehealth physical therapy by patients with chronic low back pain [ 27 ], and ongoing supervision provides an opportunity to do so. While numerous approaches for supervision are possible, supervision of a home exercise program using this device could be accomplished through an initial on-site orientation in the home setting followed by periodic virtual sessions hosted by a qualified professional.…”
Section: Discussionmentioning
confidence: 99%